Understanding PACS2 syndrome's pathomechanism by studying E209K and E211K mutations - Zbikowski, Arkadiusz; Kowalczyk, Tomasz; Kasparek, Petr; Prohazka, Jan; Sedlacek, Radislav; Ciborowski, Michał; Cysewski, Dominik; Łukasiewicz, Kacper (Mammalian genome, 2025)
Phosphofurin acidic cluster sorting protein 2 (PACS2) plays a vital role in maintaining cellular homeostasis by regulating protein trafficking between cellular membranes. This function impacts crucial processes like apoptosis, mitochondria-endoplasmic reticulum interaction, and subsequently Ca2+ flux, lipid biosynthesis, and autophagy. Missense mutations, particularly E209K and E211K, are linked to developmental and epileptic encephalopathy-66 (DEE66), known as PACS2 syndrome. Individuals with this syndrome exhibit neurodevelopmental delay, seizures, facial dysmorphism, hypotonia, and delayed motor skills.Understanding the impact of these missense mutations on molecular processes is crucial. Studies suggest that E209K mutation decreases phosphorylation, increases the survival time of protein, and modifies protein-protein interaction, consequently leading to disruption of calcium flux and lower resistance to apoptosis induction. Unfortunately, to date, only a limited number of research groups have investigated the effects of mutations in the PACS2 gene. Current research on PACS2 syndrome is hampered by the lack of suitable models. While in vitro models using transfected cell lines offer insights, they cannot fully capture the disease's complexity.To address this, utilizing cells from individuals with PACS2 syndrome, specifically induced pluripotent stem cells (iPSCs), holds promise for understanding phenotypic diversity and developing personalized therapies. However, iPSC models may not fully capture tissue-specific effects of the E209K/E211K mutation. In vivo studies using animal models, particularly mice, could overcome these limitations.This review summarizes current knowledge about PACS2 structure and functions, explores the cellular consequences of E209K and E211K mutations, and highlights the potential of iPSC and mouse models in advancing our understanding of PACS2 syndrome.
Keywords: DEE66; Humans; Mutation, Missense; Mouse model; mutace; Ultrarare; Developmental epileptic encephalopathy-66; PACS2 syndrome; Vesicular Transport Proteins; Mutation; missense mutace; indukované pluripotentní kmenové buňky; vezikulární transportní proteiny; zvířata; Induced Pluripotent Stem Cells; Animals; lidé